McLuhan in Space : A Cultural Geography - Cavell, Richard, 1949- (Book collections on Project MUSE., 2003)
The first book to propose that Marshall McLuhan be read as a spatial theorist, McLuhan in Space argues that space is the single most consistent concept in McLuhan's vast and eclectic body of work. Richard Cavell demonstrates how McLuhan extended insights derived from advances in physics and artistic experimentation into a theory of acoustic space, which he then used to challenge the assumptions of visual space that had been produced through 500 years of print culture. The notion of acoustic space provided McLuhan with a heuristic probe of prodigious range, allowing him to examine critically the many social and cultural forms of contemporary media production. It also enabled him to cross over intellectually from the purely theoretical realm into that of artistic production, where his interests in radical notions of spatial production were shared by a range of avant garde artists from bp Nichol to Glenn Gould, from John Cage to the Fluxus artists an artistic milieu in which McLuhan increasingly came to situate his work. Cavell's book is the first to examine McLuhan's work in light of this artistic backdrop, and the first to examine his contribution to Canadian studies.